2009
DOI: 10.4049/jimmunol.0901679
|View full text |Cite
|
Sign up to set email alerts
|

Impaired NK Cytolytic Activity and Enhanced Tumor Growth in NK Lytic-Associated Molecule-Deficient Mice

Abstract: NK lytic-associated molecule (NKLAM) is a protein involved in the cytolytic function of NK cells. It is weakly expressed in resting NK cells but upon target cell stimulation or after incubation with cytokines that enhance NK killing, NKLAM mRNA levels increase and protein is synthesized and is targeted to cytoplasmic granule membranes. We have previously shown that NKLAM plays a role in perforin/granzyme-mediated cytolysis in vitro. To further investigate the function of NKLAM in NK cell-mediated cytotoxicity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Data from several labs indicate that expression of GrB [36] and IFN-γ [37] are critical factors in the anti-tumor effect of activated NK cells. Therefore, splenic mononuclear cells from C57Bl/6 and IRF3KO mice were treated with poly I:C in vitro and after 24 h, CD49b + NK cells were examined by FACS analysis for intracellular GrB and IFN-γ.…”
Section: Resultsmentioning
confidence: 99%
“…Data from several labs indicate that expression of GrB [36] and IFN-γ [37] are critical factors in the anti-tumor effect of activated NK cells. Therefore, splenic mononuclear cells from C57Bl/6 and IRF3KO mice were treated with poly I:C in vitro and after 24 h, CD49b + NK cells were examined by FACS analysis for intracellular GrB and IFN-γ.…”
Section: Resultsmentioning
confidence: 99%
“…As a higher expression of the USP18 gene was seen in chickens with a shorter survival period, induction of the gene as a direct effect of infection with a highly pathogenic virus was considered possible. On the contrary, of the genes correlating with survivability, RNF19B was considered to interact with HbcH8, which plays a similar role as E2 in the ISG15 system and might act as E3 in the ISG15 system (5,9,12,22). RNF19B would play a conflicting role against USP18 in the ISG15 system, as it increases the conjugates of the target proteins and ISG15.…”
Section: Discussionmentioning
confidence: 99%
“…IFNγ) and bacterial products such as lipopolysaccharide (LPS) [4]. Studies from our laboratory have demonstrated that NK cells from NKLAM-knock out (NKLAM-KO) mice have diminished anti-tumor activity [5]. Additionally, we have shown that NKLAM plays a role in controlling tumor metastasis [6].…”
Section: Introductionmentioning
confidence: 99%